Group/Semi- Group theory and Generalization: - (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This paper is to find original symmetric of group theory and Generalization. The Condition for agroup to be given. We give fundamental properties of group and Generalization of semi Group. We alsopresent the is Isomorphism‟s and Homomorphism of a Group .